Were warriors once low carb? Commentary on New Zealand Māori nutrition and anthropometrics over the last 150 years - Marcus Hawkins (CSIRO Publishing, 2021)
ABSTRACT Obesity is a scourge on modern society and an epidemic has exploded in the developed world over the last half century, resulting in sicker populations and economically unsustainable health expenditure. The Pacific region became colonised by Europeans from the early nineteenth century onwards and, as a consequence, 'European' foodstuffs were introduced to New Zealand Māori. This has intensified over the last 150 years; so much so, that obesity is now common among New Zealand Māori, who suffer disproportionately from the chronic diseases arising from obesity. This commentary seeks to explore and compare the 'then' and 'now' in terms of New Zealand Māori nutrition and anthropometrics. It also asks the specific questions: were New Zealand Māori originally eating a low carbohydrate healthy fat diet? and should we all now reflect on a previous dietary pattern of eating in an effort to reverse the obesity epidemic?